What does three years of hunting great cormorants, Phalacrocorax carbo, tell us? Shooting autumn‐staging birds as a means of reducing numbers locally. Issue 2 (22nd April 2014) - Bregnballe, Thomas; Hyldgaard, Alexandra M; Clausen, Kevin K; Carss, David N
Abstract BACKGROUND The population of great cormorants, Phalacrocorax carbo, has increased markedly in Europe in the last 30 years, creating conflicts primarily with fisheries' interests. Some advocate that there should be a reduction in bird numbers on anything from local to regional and pan‐European levels. The effect of attempts to reduce cormorant numbers by shooting to kill and by shooting to reinforce the scaring of birds in two Danish fjords was studied. RESULTS A total of 308, 364 and 459 cormorants were shot in the two fjords during each of three annual hunting seasons. When shooting was intensive over a series of days near the birds' main roosting and sleeping place, numbers dropped significantly compared with non‐shooting years. No significant scaring effect was detected when shooting was carried out only at random along the shores of the fjords. None of the shooting treatments had an effect on the number of cormorants occurring in subsequent years. CONCLUSION These results indicate that large efforts can be invested in shooting to scare and kill cormorants without reaching any desired reduction in numbers, in particular when the shooting is not coordinated in time and space and not undertaken at key roosting sites. © 2014 Society of Chemical Industry